Preparation method of high-thermal-conductivity hot-pressed sheet based on flexible graphite paper vertically-arranged carbon nanotube array

By growing vertically arranged carbon nanotube arrays on flexible graphite paper and combining with the vacuum hot pressing process of strong interface combination and mesophase asphalt filler, the defects such as orientation, interface, and crystallinity of macroscopic nanocarbon-based composites are solved. The problem is that it significantly improves its thermal conductivity and mechanical strength and improves thermal management performance.

CN119489572APending Publication Date: 2025-02-21TIANJIN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311043341.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing macroscopic nanocarbon-based composite materials have defects such as orientation, interface, and crystallinity, which seriously restricts their directional thermal conduction properties.

Method used

Highly thermally conductive hot-pressed sheets were prepared by growing vertically arranged carbon nanotube arrays on flexible graphite paper and forming strong interface bonds through carbon-silicon bonds, combining mesophase bitumen fillers and vacuum hot pressing process.

Benefits of technology

The interface bonding force, density and mechanical strength of the composite material are significantly improved, while improving its thermal conductivity and improving thermal management performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489572A_ABST
    Figure CN119489572A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-thermal-conductivity hot-pressed sheet based on a flexible graphite paper vertical arrangement carbon nanotube array, which comprises the following three steps: in-situ growth, vacuum impregnation and vacuum hot pressing: firstly, mixing a certain amount of polycarbosilane with a xylene solution to obtain a polycarbosilane solution; then spin coating is carried out on the two faces of the graphite paper subjected to heat treatment, a polycarbosilane coating is obtained, the polycarbosilane coating is cracked at the high temperature, and the graphite paper containing the silicon carbide coating is obtained. And then carrying out in-situ chemical vapor deposition on the two surfaces of the graphite paper containing the silicon carbide coating to grow a regularly arranged carbon nanotube array. The obtained composite material is subjected to vacuum impregnation in a mesophase pitch solution, so that gaps among the carbon nanotube arrays are fully filled with micromolecular pitch; and finally, carrying out vacuum hot pressing treatment to obtain the graphite paper / vertically-arranged carbon nanotube array high-thermal-conductivity hot-pressed sheet with high density, high thermal conductivity and high mechanical strength. The obtained three-dimensional composite material is of an obvious three-dimensional layered structure, has excellent directional heat conduction performance and mechanical strength, and plays a certain role in practical application of efficient heat management materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-thermal-conductivity hot-pressing sheet of a vertically-arranged carbon nanotube array based on flexible graphite paper, and belongs to the field of composite materials. Background Art

[0002] Thermal management system is a thermal management system based on thermodynamics and heat transfer process, which is widely used in the fields of national economy and national defense. It controls the dissipation, storage and conversion of heat in equipment and device systems. With the rapid development of science and technology, electronic components are constantly developing in the direction of miniaturization and high frequency, and multifunctional integrated circuits with ultra-high integration are constantly being developed and applied, which makes the power consumption of integrated circuits increase sharply and accumulates a lot of heat in a short time, which seriously restricts the service life of the device. Relevant research shows that the design and development of efficient thermal management materials is the key to improving thermal management systems, which not only realizes the thermal management function of equipment and device systems, but also protects equipment and devices from overheating damage.

[0003] High-efficiency thermal management materials can be divided into metal-based, ceramic-based, polymer-based and nano-carbon-based thermal conductive composite materials according to the different composite materials. Among these four high thermal conductivity composite materials, nano-carbon-based composite materials have attracted much attention due to their low density, high thermal conductivity, low thermal expansion coefficient, high mechanical strength and other advantages. Many different nano-carbon-based materials, including graphene, nanobelts, carbon nanotubes, etc., have been explored to construct three-dimensional high thermal conductivity carbon-based composite materials by arranging and assembling low-dimensional carbon materials in a directional manner. Graphite materials and their derivatives such as graphene and carbon nanotubes are considered to be one of the most suitable candidate materials for assembling three-dimensional nano-carbon-based composite materials due to their unique geometric shape, low density, and excellent thermal transmission and mechanical properties.

[0004] Three-dimensional nanocarbon-based composite materials have attracted widespread attention due to their unique three-dimensional structure and advantages such as multi-directional efficient heat conduction. Their characteristics and structural advantages also make them very suitable as efficient thermal management materials. Among them, two-dimensional graphene nanosheets have extremely high in-plane thermal conductivity, which can reach 3000-5000W / (m·k), while one-dimensional carbon nanotubes have extremely high axial thermal conductivity. Therefore, it has become a common method to prepare macroscopic ordered high thermal conductivity composite materials by combining low-dimensional graphene carbon / carbon nanotubes. For example, vertically arranged carbon nanotubes are grown on graphene films, and graphene thermal conductive films are filled with carbon nanotubes as fillers. However, macroscopic nanocarbon-based materials have defects such as orientation, interface, and crystallinity, which seriously restrict their directional thermal conduction performance. It is necessary to adopt effective strategies to reduce defects and optimize their microstructures in order to construct advanced macroscopic thermal management materials.

[0005] Therefore, it is of great significance to design and prepare a three-dimensional macroscopic nanocarbon-based composite material with the advantages of high thermal conductivity, high density, strong interface bonding, and high mechanical strength. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a high thermal conductivity hot pressing sheet of vertically arranged carbon nanotube array based on flexible graphite paper, wherein the vertically arranged carbon nanotube array forms a strong interface bond with the surface of the graphite paper through a carbon-silicon bond, and is cross-linked and welded together, effectively avoiding the loosening and falling off of the carbon nanotube array on the graphite paper, and significantly improving the interface bonding force between the two. The mesophase asphalt filler fully fills the gaps between the carbon nanotube arrays, and effectively enhances the density of the composite material under hot pressing conditions, thereby improving the thermal conductivity and mechanical strength of the composite material.

[0007] The present invention adopts the following technical solution:

[0008] The present invention relates to a method for preparing a high thermal conductivity hot pressing sheet of a vertically arranged carbon nanotube array based on flexible graphite paper, and the steps are as follows:

[0009] 1) Preparation of high thermal conductivity composite materials based on double-sided growth of vertically aligned carbon nanotubes on graphite paper: prepare a polycarbosilane solution of a certain concentration, spin-coat it on both sides of the graphite paper after thermal annealing, and then perform high-temperature pyrolysis to obtain graphite paper with double-sided silicon carbide coating. The obtained graphite paper with silicon carbide coating is placed in a tubular furnace, and a catalyst solution of a certain concentration is prepared using ferrocene as a catalyst and xylene as a solvent. After heating to 860°C in an argon / hydrogen protection environment, the catalyst solution is injected into the tube at a rate of 20 ml / h through a syringe, and kept warm for a certain period of time to obtain a composite material of graphite paper / double-sided growth of vertically aligned carbon nanotubes;

[0010] 2) Preparation of high thermal conductivity hot pressing sheet based on flexible graphite paper / vertical arrangement of carbon nanotube array: Cut the graphite paper / double-sided vertical arrangement of carbon nanotubes composite material described in step 1) into suitable sizes using a circular cutter for standby use, prepare a certain concentration of mesophase asphalt solution, and vacuum impregnate the composite material for 30-60 minutes. After the impregnation, vacuum hot pressing treatment is performed with a hot pressing pressure of 1-10Mpa and a hot pressing time of 40-60 minutes, and finally a series of high thermal conductivity hot pressing sheets are obtained.

[0011] Preferably, the concentration of polycarbosilane in the polycarbosilane solution in step 1) is 0.05 g / ml, 0.1 g / ml, or 0.15 g / ml.

[0012] Preferably, the rotation speed of the spin coating in step 1) is 4000-4500 r / min.

[0013] Preferably, in step 1), the mass ratio of ferrocene to xylene in the catalyst solution is 1:5, 1:10, or 1:15.

[0014] Preferably, the vacuum impregnation time in step 2) is 30 min, 40 min, 50 min or 60 min.

[0015] Preferably, the hot pressing pressure in step 2) is 1 MPa, 5 MPa, or 10 MPa.

[0016] Preferably, the hot pressing time in step 2) is 40 to 60 minutes.

[0017] The present invention prepares a high thermal conductivity hot pressing sheet based on a vertically arranged carbon nanotube array on flexible graphite paper through a three-step method of in-situ growth, vacuum impregnation, and vacuum hot pressing. The obtained composite material has an obvious three-dimensional layered structure, and the vertically arranged carbon nanotube array is evenly distributed on both sides of the graphite paper. The small molecule asphalt filler and the hot pressing process significantly improve the density and mechanical strength of the composite material, which plays an important role in its practical application in high-efficiency thermal management materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an optical photo of a high thermal conductivity hot pressing sheet composite material based on flexible graphite paper and vertically aligned carbon nanotube arrays;

[0019] Figure 2 A series of cross-plane thermal diffusivity graphs of high thermal conductivity hot-pressed composite materials based on flexible graphite paper vertically aligned carbon nanotube arrays; DETAILED DESCRIPTION

[0020] Six embodiments of the present invention are given below to further illustrate the present invention, but not to limit the scope of the present invention.

[0021] Example 1

[0022] 1) Preparation of high thermal conductivity composite material based on vertically aligned carbon nanotubes grown on both sides of graphite paper: Ultrasonic dispersion of 0.05 mg / mL polycarbosilane solution for 30 min, then use a spin coater to spin-coat polycarbosilane on both sides of graphite paper at a spin coating rate of 4000 r / min. Graphite paper with polycarbosilane coating is placed in a tubular furnace for calcination to obtain graphite paper with silicon carbide coating on both sides, and the graphite paper with silicon carbide coating is placed in a tubular furnace, and heated to 860°C at 10°C / min in an argon / hydrogen protection environment, and a catalyst solution with a mass ratio of ferrocene to xylene of 1:5 is injected at a rate of 20 ml / h, and kept warm for 30 min to obtain a composite material based on vertically aligned carbon nanotubes grown on both sides of graphite paper;

[0023] 2) Preparation of a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array: Cut the composite material based on graphite paper double-sided growth vertically aligned carbon nanotubes described in step 1) into a suitable size, prepare a certain concentration of mesophase pitch solution, and vacuum impregnate the composite material for 30 minutes. Then, the composite material is hot pressed, the hot pressing pressure is set to 1Mpa, and the hot pressing time is 40 minutes to obtain a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array.

[0024] Example 2

[0025] 1) Preparation of high thermal conductivity composite material based on vertically aligned carbon nanotubes grown on both sides of graphite paper: Ultrasonic dispersion of 0.1 mg / mL polycarbosilane solution for 30 min, then use a spin coater to spin-coat polycarbosilane on both sides of graphite paper at a spin coating rate of 4000 r / min. Graphite paper with polycarbosilane coating is placed in a tubular furnace for calcination to obtain graphite paper with silicon carbide coating on both sides, and the graphite paper with silicon carbide coating is placed in a tubular furnace, and heated to 860°C at 10°C / min in an argon / hydrogen protection environment, and a catalyst solution with a mass ratio of ferrocene to xylene of 1:10 is injected at a rate of 20 ml / h, and kept warm for 30 min to obtain a composite material based on vertically aligned carbon nanotubes grown on both sides of graphite paper;

[0026] 2) Preparation of a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array: Cut the composite material based on graphite paper double-sided growth vertically aligned carbon nanotubes described in step 1) into a suitable size, prepare a certain concentration of mesophase pitch solution, and vacuum impregnate the composite material for 40 minutes. Then, the composite material is hot pressed, the hot pressing pressure is set to 5Mpa, and the hot pressing time is 50 minutes to obtain a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array.

[0027] Example 3

[0028] 1) Preparation of high thermal conductivity composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper: Ultrasonic dispersion of 0.15 mg / mL polycarbosilane solution for 30 min, then use a spin coater to spin-coat polycarbosilane on both sides of the graphite paper at a spin coating rate of 4500 r / min. The graphite paper with polycarbosilane coating is placed in a tubular furnace for calcination to obtain graphite paper with double-sided silicon carbide coating, the graphite paper with silicon carbide coating is placed in a tubular furnace, and the temperature is raised to 860°C at 10°C / min in an argon / hydrogen protection environment, and a catalyst solution with a mass ratio of ferrocene to xylene of 1:15 is injected at a rate of 20 ml / h, and the mixture is kept warm for 30 min to obtain a composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper;

[0029] 2) Preparation of a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array: Cut the composite material based on graphite paper double-sided growth vertically aligned carbon nanotubes described in step 1) into a suitable size, prepare a certain concentration of mesophase pitch solution, and vacuum impregnate the composite material for 50 minutes. Then, the composite material is hot pressed, the hot pressing pressure is set to 10Mpa, and the hot pressing time is 50 minutes to obtain a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array.

[0030] Example 4

[0031] 1) Preparation of high thermal conductivity composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper: Ultrasonic dispersion of 0.15 mg / mL polycarbosilane solution for 30 min, then use a spin coater to spin-coat polycarbosilane on both sides of the graphite paper at a spin coating rate of 4500 r / min. The graphite paper with polycarbosilane coating is placed in a tubular furnace for calcination to obtain graphite paper with double-sided silicon carbide coating, the graphite paper with silicon carbide coating is placed in a tubular furnace, and the temperature is raised to 860°C at 10°C / min in an argon / hydrogen protection environment, and a catalyst solution with a mass ratio of ferrocene to xylene of 1:15 is injected at a rate of 20 ml / h, and the mixture is kept warm for 30 min to obtain a composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper;

[0032] 2) Preparation of high thermal conductivity hot pressing sheet based on flexible graphite paper / vertical arrangement of carbon nanotube array: Cut the composite material based on graphite paper double-sided growth vertical arrangement of carbon nanotubes described in step 1) into suitable sizes, prepare a certain concentration of mesophase pitch solution, and vacuum impregnate the composite material for 60 minutes. Then, the composite material is hot pressed, the hot pressing pressure is set to 5Mpa, and the hot pressing time is 60 minutes to obtain a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertical arrangement of carbon nanotube array.

[0033] Example 5

[0034] 1) Preparation of high thermal conductivity composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper: Ultrasonic dispersion of 0.05 mg / mL polycarbosilane solution for 30 min, then use a spin coater to spin-coat polycarbosilane on both sides of graphite paper at a spin coating rate of 4000 r / min. Graphite paper with polycarbosilane coating is placed in a tubular furnace for calcination to obtain graphite paper with double-sided silicon carbide coating, and the graphite paper with silicon carbide coating is placed in a tubular furnace, and heated to 860°C at 10°C / min under argon / hydrogen protection, and a catalyst solution with a mass ratio of ferrocene to xylene of 1:15 is injected at a rate of 20 ml / h, and kept warm for 30 min to obtain a composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper;

[0035] 2) Preparation of a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array: Cut the composite material based on graphite paper double-sided growth vertically aligned carbon nanotubes described in step 1) into a suitable size, prepare a certain concentration of mesophase pitch solution, and vacuum impregnate the composite material for 50 minutes. Then, the composite material is hot pressed, the hot pressing pressure is set to 1Mpa, and the hot pressing time is 60 minutes to obtain a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array.

[0036] Example 6

[0037] 1) Preparation of high thermal conductivity composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper: Ultrasonic dispersion of 0.1 mg / mL polycarbosilane solution for 30 min, then use a spin coater to spin-coat polycarbosilane on both sides of graphite paper at a spin coating rate of 4000 r / min. Graphite paper with polycarbosilane coating is placed in a tubular furnace for calcination to obtain graphite paper with double-sided silicon carbide coating, and the graphite paper with silicon carbide coating is placed in a tubular furnace, and heated to 860°C at 10°C / min in an argon / hydrogen protection environment, and a catalyst solution with a mass ratio of ferrocene to xylene of 1:15 is injected at a rate of 20 ml / h, and kept warm for 30 min to obtain a composite material based on double-sided growth of vertically aligned carbon nanotubes on graphite paper;

[0038] 2) Preparation of a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array: Cut the composite material based on graphite paper double-sided growth vertically aligned carbon nanotubes described in step 1) into a suitable size, prepare a certain concentration of mesophase pitch solution, and vacuum impregnate the composite material for 40 minutes. Then, the composite material is hot pressed, the hot pressing pressure is set to 5Mpa, and the hot pressing time is 60 minutes to obtain a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array.

Claims

1. A method for preparing a high thermal conductivity hot pressing sheet of vertically aligned carbon nanotube array based on flexible graphite paper, characterized in that The preparation steps are as follows: 1) Preparation of high thermal conductivity composite materials based on double-sided growth of vertically aligned carbon nanotubes on graphite paper: prepare a polycarbosilane solution of a certain concentration, spin-coat it on both sides of the graphite paper after thermal annealing, and then perform high-temperature pyrolysis to obtain graphite paper with double-sided silicon carbide coating. The obtained graphite paper with silicon carbide coating is placed in a tubular furnace, and a catalyst solution of a certain concentration is prepared using ferrocene as a catalyst and xylene as a solvent. After heating to 860°C in an argon / hydrogen protection environment, the catalyst solution is injected into the tube at a rate of 20 ml / h through a syringe, and kept warm for a certain period of time to obtain a composite material of graphite paper / double-sided growth of vertically aligned carbon nanotubes; 2) Preparation of high thermal conductivity hot pressing sheet based on flexible graphite paper / vertical arrangement of carbon nanotube array: Cut the graphite paper / double-sided vertical arrangement of carbon nanotubes composite material described in step 1) into suitable sizes using a circular cutter for standby use, prepare a certain concentration of mesophase asphalt solution, and vacuum impregnate the composite material for 30-60 minutes. After the impregnation, vacuum hot pressing treatment is performed with a hot pressing pressure of 1-10Mpa and a hot pressing time of 40-60 minutes, and finally a series of high thermal conductivity hot pressing sheets are obtained.

2. The preparation method according to claim 1, characterized in that The concentration of polycarbosilane in the polycarbosilane solution in step 1) is 0.05 g / ml, 0.1 g / ml, and 0.15 g / ml.

3. The preparation method according to claim 1, characterized in that The rotation speed of the spin coating in step 1) is 4000-4500 r / min.

4. The preparation method as claimed in claim 1, characterized in that the mass ratio of ferrocene to xylene in the catalyst solution of step 1) is 1:5, 1:10, or 1:

15.

5. The preparation method according to claim 1, characterized in that Step 2) The vacuum impregnation time is 30 min, 40 min, 50 min, and 60 min.

6. The preparation method according to claim 1, characterized in that Step 2) hot pressing pressure is 1Mpa, 5Mpa, 10Mpa.

7. The preparation method according to claim 1, characterized in that Step 2) The hot pressing time is 40 to 60 minutes.

8. According to the preparation method described in claim 1, a high thermal conductivity hot pressing sheet based on flexible graphite paper / vertically aligned carbon nanotube array is obtained, and the obtained composite material has a distinct three-dimensional layered structure, and the vertically aligned carbon nanotube arrays are evenly distributed on both sides of the graphite paper. The small molecule asphalt filler and the hot pressing process significantly improve the density and mechanical strength of the composite material, which plays an important role in its practical application in high-efficiency thermal management materials.

Citation Information

Cited By

  • Multi-zone independent temperature control carbon fiber composite material hot press molding press

    CN120863108A